(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article analyzes the unique character and characteristics of children in Anvar Obidjon’s poems. The colorful spiritual world of children and the meanings of symbolic details are explained.